Caracterização e modificações químicas da proteína da microalga spirulina (Spirulina máxima) - Carvajal, Juan Carlos Letelier (2009)
Maximum Spirulina is an unicellular microalga, that she has form of helical filament and that she grows in waters strongly alkaline; she belongs to the cianobacterial group, cianofíceas or algae green-blued and they have been used since times many old. The microalgae presented a biomass growth in summer of 1,07 g/L and a 23,63% of rental. Present a high contend of proteins (54.93%) and low oils content (6,84%) and ashes (13,05%), this content of proteins rises in the flour degreased for 61,14%. being Fractioned the proteins was obtained majority incomes of albumins (36,61%), basic glutelina (31,29%) and globulin (21,03%), and minority of prolaminas (3,95%) and acid glutelina (0,29%). In the obtaining of the isolated proteic, the index in extracted total protein in the three extractions was 54,36%, the index of precipitation isoelectric in the extract of pH 10,0 was 46,81% and the index of total protein in the isolated proteic was of 95,44% in pH 10,0. the analysis of the molecular weight of the proteins of the flour in PAGE-SDS - she revealed from 8 to 13 bands. The subunidades of 16,21 and 15,74 kDa appeared prominent in the sample. The term-stability (Td, ºC) and the variation entálpica (H, KCal/g), examined by DSC, respective the degreased flour and isolated proteic were of 104,58°C and 102,47°C and 0,65 Kcal.g-1 and 0,59 Kcal.g-1, respectively. The nutritional characterization of the protein of maximum Spirulina, they demonstrated a content of tannins of 17,5 mg.g-1 and absence of the lectina inhibitors and tripsina. The composition of amino acids revealed her witnesses of all of the essential amino acids in superior amounts to the pattern FAO/WHO/UNU, with predominance of the leucina (3,96g/100g protein), fenilalanina (2,92 g/100g proteins) and valina (2,71 g/100 g proteins). The results of the chemical modifications revealed that the acetilation was shown more it executes than the succinylation in the different modification degrees (1; 2.5; 5; 10 and 15%). the solubility of the isolated not modified indicated a point isoelectric (low solubility) in pH 5,0, for the isolated ones modified the point isoelectric was observed in the pH 4,0. the solubility increased with the chemical modification, being observed a larger increase in the succinylation. The capacity of absorption of water was influenced positively with the chemical modification, being observed a larger increase in the acetilation in relation to succinylation. In the same way the capacity of oil absorption increases with the modification, being observed a larger increase of the capacity in the acetilation. The emulsion capacity increased with the chemical modification in all of the modification degrees, being observed a light increase in the succinylation. The emulsion activity was increased with the chemical modification, being observed a light increase in the succinylation. The stability of the emulsion increased with the chemical modification, being observed a larger increase in the succinylation. The relative viscosity of the isolated modified proteic increased with the concentration of the protein solution, with to room temperature and with the heating (90ºC), in the measure that increases the modification degree, it also increases the viscosity. The floaming capacity increased with the chemical modification, being observed a larger index in the succinylation, in the espumação stability is noticed that the decrease in the stability was less accentuated in the acetilation than in the succinylation, in all of the analyzed times and all of the modification degrees tested. The protein of maximum Spirulina presented a chemical and nutritional characteristic satisfactory in relation to minimum demands established by the international organisms.